Framing complexity in Formative Mesoamerica - DeLance, Lisa, editor; Feinman, Gary M., editor; University Press of Colorado, publisher (Colorado State University. Libraries, 2022)
An examination of variable social and economic processes, Framing Complexity in Formative Mesoamerica explores nascent social complexity during the Preclassic/Formative period in Mesoamerica and addresses broader social questions about egalitarian and transegalitarian Pre-hispanic Mesoamerican cultural groups. The chapters explore social aggregation, emergence of ethnic affiliations, and regional and macro-regional variability.--Provided by publisher.
Framing complexity / Lisa L DeLance -- Heterarchy and the emergence of social complexity in Formative period coastal Oaxaca, Mexico / Guy David Hepp -- Pottery and society during the Preclassic period at Yaxuná, Yucatán / Travis W. Stanton, Sara Dzul Góngora, Ryan H. Collins, Rodrigo Martín Morales -- The emergence of complex imagery on late Terminal Formative gray ware pottery from coastal Oaxaca, Mexico / Jeffrey S. Brzezinski, Sarah B. Barber, Arthur A. Joyce -- The beginnings of complexity in the central Petén Lakes area / Prudence M. Rice, Katherine E. South -- Shifting ceramic styles in the Formative period Basin of Mexico / Wesley D. Stoner, Deborah L. Nichols -- Urban organization and origins of complexity in the Puuc Region of Northern Yucatan / Michael P. Smyth -- The role of monumental architecture and landscape modification in the development of complexity at early Xunantunich, Belize / Zoē J. Rawski, M. Kathryn Brown -- The complexity of figurines: ancestor veneration at Cahal Pech, Cayo, Belize / Lisa L. DeLance, Jamie J. Awe -- From shell beads to symbolic royal bodies: a diachronic comparison of body ornamentation production, consumption, and social complexity at prehispanic Pacbitun, Belize / Jon Spenard, George J. Micheletti, Kaitlin Crow, Terry G. Powis, Teresa Tremblay -- Why the Mesoamerican Formative period matters? Vantages on human aggregation and cooperation / Gary M. Feinman.
Keywords: Indians of Mexico -- Social conditions; Indians of Central America -- Social conditions; Indians of Mexico -- Antiquities; Indians of Central America -- Antiquities; Indigenous peoples -- Mexico; Indigenous peoples -- Central America; Excavations (Archaeology) -- Mexico; Excavations (Archaeology) -- Central America